Harnessing RSPCA Stakeholder Expertise to Co-Produce a Complex Intervention Addressing Childhood and Adolescent Animal Harm - Suzanne Lawrie; Claire Blakey; Roxanne Hawkins; Joanne M. Williams (Animals)
Childhood and Adolescent Animal Harm (CAAH) is influenced by biological, psychological and socio-environmental risk factors. Interventions to prevent animal harm among children and young people are essential for fostering empathy and reducing future harm. This study explores the perspectives of RSPCA stakeholders, to co-produce a redeveloped version of ‘Breaking the Chain’, an intervention addressing youth animal harm. Semi-structured interviews were conducted with 16 RSPCA employees across a range of departments and geographical locations in England, UK. Thematic analysis was used to identify key insights on target groups, intervention content, delivery methods, and evaluation strategies. Two primary target groups were identified: universal audiences (primary school-aged children) and high-risk youth. Participants advocated for retaining the core content of the existing intervention while modernising resources to address contemporary risk factors, such as online exposure to animal harm while ensuring accessibility for neurodiverse audiences. Face-to-face delivery was favoured, complemented by digital resources. Evaluation was viewed as critical, with a focus on both short-term outcomes and long-term impact. This study highlights the importance of stakeholder involvement in co-producing effective cruelty prevention interventions. Future steps will involve a coproduction study with children and young people to gather their perspectives on the intervention redesign. This will be followed by a pilot and evaluation of the redesigned intervention, incorporating feedback from both the implementers (e.g., teachers, youth offending teams, RSPCA employees) and the recipients (children and young people).